A Trishistidine Pseudopeptide with Ability to Remove Both CuΙ and CuΙΙ from the Amyloid‐β Peptide and to Stop the Associated ROS Formation. Issue 67 (9th November 2017) - Conte‐Daban, Amandine; Boff, Bastien; Candido Matias, Andreza; Aparicio, Claudia N. Montes; Gateau, Christelle; Lebrun, Colette; Cerchiaro, Giselle; Kieffer, Isabelle; Sayen, Stéphanie; Guillon, Emmanuel; Delangle, Pascale; Hureau, Christelle
Abstract: The pseudopeptideL, derived from a nitrilotriacetic acid scaffold and functionalized with three histidine moieties, is reminiscent of the amino acid side chains encountered in the Alzheimer's peptide (Aβ). Its synthesis and coordination properties for Cu Ι and Cu ΙΙ are described.L efficiently complex Cu ΙΙ in a square‐planar geometry involving three imidazole nitrogen atoms and an amidate–Cu bond. By contrast, Cu Ι is coordinated in a tetrahedral environment. The redox behavior is irreversible and follows an ECEC mechanism in accordance with the very different environments of the two redox states of the Cu center. This is in line with the observed resistance of the Cu Ι complex to oxidation by oxygen and the Cu ΙΙ complex reduction by ascorbate. The affinities ofL for Cu ΙΙ and Cu Ι at physiological pH are larger than that reported for the Aβ peptide. Therefore, due to its peculiar Cu coordination properties, the ligandL is able to target both redox states of Cu, redox silence them and prevent reactive oxygen species production by the CuAβ complex. Because reactive oxygen species contribute to the oxidative stress, a key issue in Alzheimer's disease, this ligand thus represents a new strategy in the long route of finding molecular concepts for fighting Alzheimer's disease. Abstract : No escape for Cu ! A peptide‐like ligand with three histidine residues targets both redox states of Cu‐bound to the Alzheimer's peptide and redox silence them.